2015
DOI: 10.1021/acs.chemmater.5b00329
|View full text |Cite
|
Sign up to set email alerts
|

Halogenation of a Nonplanar Molecular Semiconductor to Tune Energy Levels and Bandgaps for Electron Transport

Abstract: Though peripheral halogen substitution is a known strategy to lower the lowest unoccupied (LUMO) and highest occupied (HOMO) molecular orbital energy levels of planar molecular semiconductors, this strategy has not been explored in conformationally contorted systems. We demonstrate that substitution of peripheral hydrogens with fluorine and chlorine can effectively lower the energy levels of contorted hexabenzocoronene (cHBC) despite its nonplanar conformation. The HOMO energy level lowers comparably with fluo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
72
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 76 publications
3
72
1
Order By: Relevance
“…The computational and the experimental data were listed in Table S2 and plotted in Figure S2. The results showed that the maximum absorption wavelength of PBE0 was 433 nm, which is in good accordance with the experimental value 400 nm . Therefore, the absorption spectra of 1–14 were simulated by TD‐PCM‐PBE0/6‐31G(d) method.…”
Section: Methodssupporting
confidence: 81%
See 2 more Smart Citations
“…The computational and the experimental data were listed in Table S2 and plotted in Figure S2. The results showed that the maximum absorption wavelength of PBE0 was 433 nm, which is in good accordance with the experimental value 400 nm . Therefore, the absorption spectra of 1–14 were simulated by TD‐PCM‐PBE0/6‐31G(d) method.…”
Section: Methodssupporting
confidence: 81%
“…The results are shown in Table S1. Meantime, B3LYP has been proven feasible to predict the geometries and the electronic structures of HBC derivatives . The absorption spectra and excited‐state energies were obtained with TD‐DFT calculations based on the optimized ground‐state geometries .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Organochlorine compounds are vital as polymer precursors [1], as pharmaceuticals [23] and agrochemicals [46] and as functional materials [78]. And as there is an abundance of chlorine-containing natural products, the synthesis of chlorinated functional groups, such as allyl- and vinyl chlorides, can represent challenging obstacles that practitioners of natural product synthesis must surmount [912].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9] Generally, the thickness of organic semiconductor layer in organic electronic devices is in the range of several tens of to hundreds of nanometer (nm), which consists of tens of or more molecular layers. [10][11][12][13][14][15][16] On the other hand, ultrathin film (< 15 nm, Figure 1a) of organic semiconductors represents a kind of nano-scale film consisting of monolayer to few molecular layers (Figure 1b).…”
Section: Introductionmentioning
confidence: 99%